2002
DOI: 10.1128/jvi.76.1.392-396.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Change in the Nuclear Localization Sequence of the nsP2 Protein Affects the Neurovirulence of Semliki Forest Virus

Abstract: The replicase protein nsP2 of Semliki Forest virus (SFV) has a 648 RRR nuclear localization signal and is transported to the nucleus. SFV-RDR has a single amino acid change which disrupts this sequence and nsP2 nuclear transport. In BHK cells, SFV4 and SFV-RDR replicate to high titers, but SFV-RDR is less virulent in mice. We compared the replication of SFV4 and SFV-RDR in adult mouse brain. Both SFV4 and SFV-RDR were neuroinvasive following intraperitoneal inoculation. SFV4 spread rapidly throughout the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 41 publications
4
59
0
Order By: Relevance
“…Our experiments provided evidence that nsP2 is one of the proteins that determine the level of IFN-␣/␤ release. These data correlate with recently published results on the replication of Semliki Forest virus mutants in mouse brains (14). These experiments indicated that mutations in a nuclear localization signal of nsP2 either make the virus more sensitive to interferon or lead to more-efficient induction of IFN-␣/␤.…”
Section: Discussionsupporting
confidence: 81%
“…Our experiments provided evidence that nsP2 is one of the proteins that determine the level of IFN-␣/␤ release. These data correlate with recently published results on the replication of Semliki Forest virus mutants in mouse brains (14). These experiments indicated that mutations in a nuclear localization signal of nsP2 either make the virus more sensitive to interferon or lead to more-efficient induction of IFN-␣/␤.…”
Section: Discussionsupporting
confidence: 81%
“…It has been controversial whether SFV or SIN kills host cells via receptor binding/endocytosis or RNA replication. [25][26][27] By infecting 3T9 mouse embryonic fibroblasts (MEFs) with ultraviolet (UV)-inactivated SFV and monitoring virus uptake, RNA replication and apoptosis induction, we clearly show that SFV requires an intact RNA genome to induce classical features of apoptosis (Supplementary Material and Supplementary Figure 1). Effective apoptosis is mediated via the activation of caspases.…”
Section: Resultsmentioning
confidence: 99%
“…Point mutations in nsP2 attenuate or suppress both the cytotoxicity and the shut-off of host protein synthesis, and therefore such mutations may be the basis for the development of new, less cytotoxic and non-cytotoxic SFV and SIN vectors. 27,37 However, as nsP2 is also essential for RNA replication, it cannot be discriminated if its cytotoxic action is due to the lack of RNA production, the inhibition of protein synthesis or the processing/activation of initiator or effector caspases. Here we obtained evidence that inhibition of protein synthesis is not sufficient to trigger the apoptotic program.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a single amino acid change in (i) the envelope glycoprotein of Sindbis virus or lymphocytic choriomeningitis virus, (ii) the HA protein of avian influenza A virus, or (iii) the nsP2 replicase of Semliki Forest virus (or two amino acid changes in the envelope glycoprotein of dengue virus) changes the severity of neurovirulence outcomes (16,21,30,31,54). The specific role that each BDV gene plays in neurovirulence and BD phenotype remains poorly characterized.…”
Section: Discussionmentioning
confidence: 99%